The disturbance of intestinal microbiome caused by the novel duck reovirus infection in Cherry Valley ducklings can induce intestinal damage - Lijie Li; Baishi Lei; Wuchao Zhang; Weizhu Wang; Chuanchuan Shang; Yibin Hu; Kuan Zhao; Wanzhe Yuan (Poultry Science)
Novel duck reovirus disease is an infectious disease mainly caused by novel duck reovirus (NDRV), which is characterized by spleen necrosis and persistent diarrhea in ducks. However, the pathogenic mechanism of NDRV infection in Cherry Valley ducks remains unclear. To investigate the distribution of NDRV in the intestines of Cherry Valley ducks, intestinal morphogenesis, intestinal permeability, inflammatory cytokines, and the expression of tight junction proteins (TJPs), we introduced NDRV via intramuscular infection. The diversity and composition of ileum flora and content of short-chain fatty acids (SCFAs) were analyzed using Illumina MiSeq sequencing. The relationship between changes in the intestinal microbial community and intestinal damage in Cherry Valley ducks infected with NDRV was also assessed to offer new insights into the pathogenesis of NDRV and intestinal flora composition. The results showed that intestinal inflammation and barrier dysfunction occurred following NDRV infection. Additionally, a significant reduction in dominant bacterial species and a decrease in SCFA content within the intestinal microbiota led to weakened colonization resistance and the enrichment of opportunistic pathogens, exacerbating intestinal damage post-NDRV infection. Notably, TJPs and inflammatory cytokine disruptions were linked to a decline in SCFA-producing bacteria and an accumulation of pathogenic bacteria. In summary, changes in the ileum intestinal flora and disruptions to the intestinal barrier were associated with NDRV infection. Consequently, disturbances in intestinal flora caused by NDRV infection can lead to intestinal damage. These findings may offer us a new perspective, targeting the gut microbiota to better understand the progression of NDRV disease and investigate its underlying pathogenesis.